Comparison of Conventional and Adaptive Hysteresis Current Control Methods for Power Quality Improvement using Active Filters - Handoko, Susatyo; Winardi, Bambang (Advance Sustainable Science Engineering and Technology, 2025)
Hysteresis is widely applied in converter control techniques because of its simplicity and stability. This paper discusses hysteresis current control applied to single-phase active filters. Active filters are designed for harmonic mitigation and reactive power compensation. Simulation and comparison of conventional hysteresis control (constant hysteresis band - variable frequency) and adaptive hysteresis (variable hysteresis band - constant frequency) on active filters were carried out. Simulations were carried out using MATLAB Simulink. The simulation results show that the active filter can work well when using conventional or adaptive hysteresis current control. This is indicated by a decrease in the THDI of the source current and an increase in the power factor on the source side. From the simulations carried out, with a maximum source current THDI target of 5% according to the IEEE 519 standard, the hysteresis band required for conventional hysteresis control is 0.5 A, and the switching frequency required for adaptive hysteresis control is 120 kHz. By increasing the power factor to unity, it results in a reduction in reactive losses in the system. These findings are significant in advancing more efficient power quality control strategies, reducing harmonic distortion and improving power factor in electrical systems. Such improvements contribute directly to the development of more sustainable and resilient electrical infrastructures.